Central Cell in Flowering Plants: Specification, Signaling, and Evolution - Li, Hong-Ju; Yang, Wei-Cai (Frontiers in Plant Science, 2020)
During the reproduction of animals and lower plants, one sperm cell usually outcompetes the rivals to fertilize a single egg cell. But in flowering plants, two sperm cells fertilize the two adjacent dimorphic female gametes, the egg and central cell, respectively, to initiate the embryo and endosperm within a seed. The endosperm nourishes the embryo development and is also the major source of nutrition in cereals for humankind. Central cell as one of the key innovations of flowering plants is the biggest cell in the multicellular haploid female gametophyte (embryo sac). The embryo sac differentiates from the meiotic products through successive events of nuclear divisions, cellularization, and cell specification. Nowadays, accumulating lines of evidence are raveling multiple roles of the central cell rather than only the endosperm precursor. In this review, we summarize the current understanding on its cell fate specification, intercellular communication, and evolution. We also highlight some key unsolved questions for the further studies in this field.